The risks of adverse events with venlafaxine for adults with major depressive disorder: a systematic review of randomised clinical trials with meta-analysis and Trial Sequential Analysis - C. B. Kamp; J. J. Petersen; P. Faltermeier; S. Juul; F. Siddiqui; J. Moncrieff; M. A. Horowitz; M. P. Hengartner; I. Kirsch; C. Gluud; J. C. Jakobsen (Cambridge University Press, 2024)
Abstract Aims Venlafaxine is used to treat depression worldwide. Previous reviews have demonstrated that venlafaxine lowers scores on depression rating scales, producing statistically significant results but the relevance to patients remains uncertain. Knowledge of the incidence of the adverse effects associated with venlafaxine has previously been based on the results of non-randomised studies. Our primary objective was to assess the risks of adverse events with venlafaxine in the treatment of adults with major depressive disorder in randomised trials. Methods We searched relevant databases and other sources from inception to 7 March 2024 for randomised clinical trials comparing venlafaxine versus placebo or no intervention in adults with major depressive disorder. Data were synthesised using meta-analysis and Trial Sequential Analysis. The primary outcomes were suicides or suicide attempts, serious adverse events and non-serious adverse events. Results We included 28 trials randomising 6,253 participants to venlafaxine versus placebo. All results were at high risk of bias, and the certainty of the evidence was very low. All trials assessed outcomes at a maximum of 12 weeks after randomisation. Meta-analysis and Trial Sequential Analysis showed insufficient information to assess the effects of venlafaxine on the risks of suicides or suicide attempts. Meta-analysis showed evidence of harm of venlafaxine versus placebo on serious adverse events (risk ratio: 2.66; 95% confidence interval: 1.67-4.25; p < 0.01; 22 trials), mainly due to a higher risk of sexual dysfunction and anorexia. Meta-analysis showed that venlafaxine also increased the risk of several non-serious adverse events: nausea, dry mouth, dizziness, sweating, somnolence, constipation, nervousness, insomnia, asthenia, tremor and decreased appetite. Conclusions Short-term results show that venlafaxine has uncertain effects on the risks of suicides but increases the risks of serious adverse events (especially sexual dysfunction and anorexia) and many non-serious adverse events. The long-term effects of venlafaxine for major depressive disorder are unknown. It is a particular cause for concern that there are no data on the long-term adverse effects of venlafaxine given that so many people use these drugs for several years.